2014
DOI: 10.1001/jamasurg.2013.4249
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Risk-Adjusted Outcomes for Profiling Hospital Surgical Quality

Abstract: IMPORTANCE Quality improvement platforms commonly use risk-adjusted morbidity and mortality to profile hospital performance. However, given small hospital caseloads and low event rates for some procedures it is unclear whether these outcomes reliably reflect hospital performance. OBJECTIVE To determine the reliability of risk-adjusted morbidity and mortality for hospital performance profiling using clinical registry data. DESIGN Retrospective cohort study SETTING/DATA SOURCE American College of Surgeons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 26 publications
0
57
1
Order By: Relevance
“…10 This retrospective study could not assess the role of routine preoperative blood tests, ASA class, or any other preoperative risk score in outcome prediction. Furthermore, the reliability of predicting outcomes by using registry-based data has been questioned by others 5 and even by the authors themselves, 10 specifically since in many large registries detailed preoperative patient data are lacking. Another major problem is that the type and rate of complications in neurosurgery are variable but limited.…”
mentioning
confidence: 99%
“…10 This retrospective study could not assess the role of routine preoperative blood tests, ASA class, or any other preoperative risk score in outcome prediction. Furthermore, the reliability of predicting outcomes by using registry-based data has been questioned by others 5 and even by the authors themselves, 10 specifically since in many large registries detailed preoperative patient data are lacking. Another major problem is that the type and rate of complications in neurosurgery are variable but limited.…”
mentioning
confidence: 99%
“…15 Review of morbidities and mortality has been the primary method of assessing surgical quality used by physicians, hospitals, and oversight agencies. 10,17,20 In recent years, the reoperation rate, defined as the percentage of patients undergoing a new operation, has been proposed as a quality indicator, a surrogate for surgical adverse events. 4,13,19,24 General surgery has been at the forefront of assessing reoperations.…”
mentioning
confidence: 99%
“…sample size) at most hospitals and low rates of most adverse events. 2,3 As a result, an emphasis has been placed on considering reliability when selecting outcome measures. 4,5,[14][15][16] In contrast to other clinical outcome measures, we have demonstrated that episode payments are more reliable and many hospitals meet commonly accepted reliability benchmarks, even for less common procedures such as pancreatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 While the reliability of outcome measures such as 30-day mortality and complications for surgical procedures have been investigated, the reliability of total episode payments, a measure that is associated with each episode of care, has not yet been explored. [3][4][5][6] A better understanding of surgical episode payment reliability would provide additional information on how confidently this proposed quality metric could be used to compare providers, establishing an additional metric for assessing episode efficiency. This has important implications in helping Accountable Care Organizations (ACO) and hospitals interested in bundled payments understand potential liabilities and opportunities for improvement under these newer payment strategies.…”
Section: Introductionmentioning
confidence: 99%